Supercritical CO2 extraction of steroidal sapogenins from fenugreek (Trigonella foenum-graecum L.)seed - Bogdanović Aleksandra; Tadić Vanja; Petrović Slobodan; Skala Dejan (Chemical Industry and Chemical Engineering Quarterly, 2020)
Supercritical CO2 extraction was applied on fenugreek (Trigonella foenum-graecum L., Fabaceae) seeds with the aim to define optimal process conditions to obtain the maximal extract yields content of steroidal sapogenins. Central composite rotatable design (CCRD) combined with response surface methodology (RSM) was applied to determine optimal process conditions defined by the influence and interaction of pressure, temperature and time of extraction through consumption of SC CO2. Optimization experiments revealed that the pressure of 24.73 MPa, the temperature of 38.°C and the consumption of SC CO2 of 19.24 g/gDM were the best process conditions enabling the maximal yield of extract and gain of the highest content of sapogenins. The optimal values of pressure and temperature defined SC CO2 density of 885.47 kg/m3, which provided the maximal yield of the extract with the highest content of steroidal sapogenins. The achieved yield of extract at these conditions was 0.073g/gDM, with 0.774 mg/gDM diosgenin, 0.477 mg/gDM protodioscin, 0.713 mg/gDM sarsapogenin and 0.205 mg/gDM oleanolic and ursolic acid with a significant quantity of 2.475 mg/gDM in the obtained extract. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III45017]